Legal Review of the Defense of Forced Excess (Noodweer Exces) in the Crime of Assault in Decision No. 4/Pid.B/2024/PN JNP - Nugroho, Fajar Seto; Isnaini, Enik; Sofyan, Mohammad Riyadi (Universitas Islam Lamongan, 2024)
ABSTRACT Noodweer excess is a condition where a person commits an unlawful act as a form of forced defense that exceeds the limit due to a threat or sudden attack. The justification for Noodweer excess is regulated in Article 49 paragraph (2) of the Criminal Code which allows the judge not to impose a sentence if there is a legitimate reason for self-defense, so that the defendant can be released from the clutches of the criminal code. This also becomes the legal basis for the judge in decision Number 4 / Pid.B / 2024 / PN JNP to provide an acquittal for the defendant who has been proven to have committed a crime that resulted in the death of a person. Based on the background above, the author proposes a formulation of the problem, namely; first, how is the regulation of forced defense beyond the limit (noodweer excess) in the Criminal Code?, second, how is the analysis of the judge's considerations in decision Number 4 / Pid.B / 2024 / PN JNP. This research method uses a normative legal research type, with a statutory approach and a conceptual approach. The legal materials used are primary legal materials including: Criminal Code and Decision Number 4/Pid.B/2024/PN JNP. From the results of the study, it can be concluded that: first, Article 49 paragraph 2 of the Indonesian Criminal Code (KUHP) regulates forced defense (noodweer excess) that exceeds the limit. The act is still against the law, but due to the conditions or reasons for the forced defense that exceeds the limit, the error is eliminated. Justifying and forgiving reasons can eliminate the criminal nature of an act. Second, Case Number 4/Pild.B/2024/PN. Jnp shows that the defendant cannot be punished because his actions meet the requirements of noodweer excess, as a response to threats with a knife from the victim. The defendant's actions are proven to meet the elements of forced defense that exceeds the limit which is carried out due to mental shock due to serious attacks or threats.